An efficient chitosan-based naphthalimide-modified fluorescent sensor for rapid detection of 2, 4-dinitrophenylhydrazine and its applications in environmental analysis. (5th September 2021) - Meng, Zhiyuan; Yin, Jie; Zhao, Fei; Li, Mingxin; Zhang, Yan; Liang, Yueyin; Wang, Zhonglong; Yang, Yiqin
Graphical abstract: Highlights: A novel chitosan-based naphthalimide-modified fluorescent probe CTS-NA-OAc was synthesized. The probe CTS-NA-OAc was turned to be a highly sensitive and selective senor for DNPH in a short time. The probe CTS-NA-OAc was successfully applied to detect DNPH in real water and soil samples. Abstract: 2, 4-Dinitrophenylhydrazine (DNPH) is widely present in the ecological environment and has great harmful effects on humans, so it is necessary to detect DNPH in environmental samples. Chitosan, the second abundant renewable biological material in natural, has the advantages of wide sources, good biodegradability and good biocompatibility. Naphthalimide is a kind of classical fluorophore and has widely applications in fluorescent probe field. In this paper, a new fluorescent probe CTS-NA-OAc for DNPH detection was developed, which was constructed by using chitosan as skeleton and naphthalimide as the fluorophore. This probe displayed a highly specific "turn-off" fluorescence response toward DNPH, accompanied by the fluorescence color change from green to colorless. Its detection limit for DNPH was calculated to be 4.9 × 10 −7 M and much lower than that of the corresponding model compound NA-OAc . The interference experiments showed that other competing analytes have no influence on the detection of DNPH in a complex environment. In addition, the coordination mechanism of CTS-NA-OAc with DNPH was investigated by 1 H NMR titration and DFT calculations. Inspired by the above prominent performances, the probe CTS-NA-OAc was successfully applied to the detection of DNPH in real water and soil samples.